NEW EXPERIENCES IN CREATING ARTISTIC-PUBLICIST FILMS - Gavkhar Nazarova (Social science and innovation, 2023)
This article, based on scientific sources, provides information about art-journalistic documentaries and their features. Historical figure, creator, public figure, politician, military man; A film about a figure of state and society – Islam Khuja - is analyzed.